Optimal power flow via interior-exterior method - De Sousa, V. A.; Baptista, Edméa Cássia [UNESP]; Da Costa, G. R M (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This paper presents a new approach to the resolution of the Optimal Power Flow problem. In this approach the inequality constraints are treated by the Modified Barrier and Primal-Dual Logarithmic Barrier methods. The inequality constraints are transformed into equalities by introducing positive auxiliary variables, which are perturbed by the barrier parameter. A Lagrangian function is associated with the modified problem. The first-order necessary conditions are applied to the Lagrangian, generating a nonlinear system which is solved by Newton's method. The perturbation of the auxiliary variables results in an expansion of the feasible set of the original problem, allowing the limits of the inequality constraints to be reached. Numerical tests on the Brazilian CESP and South-Southeast systems and a comparative test indicated that the new approach efficiently resolves of the Optimal Power Flow problem. © 2007 IEEE.
Keywords: Modified barrier function; Optimal power flow; Perturbation of constraints; Primal-dual method; Nonlinear systems; Numerical methods; Parameter estimation; Perturbation techniques; Problem solving; Electric power transmission